Murine Ccl2/Cx3cr1 Deficiency Results in Retinal Lesions Mimicking Human Age-Related Macular Degeneration - Tuo, Jingsheng (2007)
PURPOSE: Senescent Ccl2(-/-) mice are reported to develop cardinal features of human age-related macular degeneration (AMD). Loss-of-function single-nucleotide polymorphisms within CX3CR1 are also found to be associated with AMD. The authors generated Ccl2(-/-)/Cx3cr1(-/-) mice to establish a more characteristic and reproducible AMD model. METHODS: Single Ccl2- and Cx3cr1-deficient mice were crossbred to obtain Ccl2(-/-)/Cx3cr1(-/-) mice. Funduscopy, histopathology, retinal A2E quantification, proteomics, RT-PCR gene expression assay, immunochemistry, and Western blotting were used to examine the retina and to evaluate gene expression within the retinal tissue. RESULTS: By 6 weeks of age, all Ccl2(-/-)/Cx3cr1(-/-) mice developed AMD-like retinal lesions, including drusen, retinal pigment epithelium alteration, and photoreceptor degeneration. Furthermore, choroidal neovascularization occurred in 15% of the mice. These degenerative lesions progressed with age. A2E, a major lipofuscin fluorophore that accumulated during AMD progression, was significantly higher in the Ccl2(-/-)/Cx3cr1(-/-) retina than in the wild-type retina. Complement cofactor was higher in the Ccl2(-/-)/Cx3cr1(-/-) RPE. Proteomics data indicated that four proteins were differentially expressed in Ccl2(-/-)/Cx3cr1(-/-) retina compared with control. One of these proteins, ERp29, an endoplasmic reticulum protein, functions as an escort chaperone and in protein folding. CONCLUSIONS: The authors concluded that Ccl2(-/-)/Cx3cr1(-/-) mice develop a broad spectrum of AMD abnormalities with early onset and high penetrance. These observations implicate certain chemokines and endoplasmic reticulum proteins in AMD pathogenesis. Similar to the mechanism of neurodegeneration caused by dysfunction of endoplasmic reticulum proteins, decreased chaperoning may cause misfolded protein accumulation, leading to drusen formation and retinal degeneration.